Cost Accounting Information System Effectiveness Under Public Higher Education Organizational Restructuring - Mohammed Hazim Issmeil Al-Ghazali; Faeq Malallah Mahmood Albalaki (Indonesian Journal of Law and Economics Review, 2026)
General Background: Public sector modernization requires robust financial information systems to improve accountability, budgeting, and resource allocation. Specific Background: The Iraqi Ministry of Higher Education and Scientific Research recently underwent significant structural expansion, creating administrative and cost control challenges. Knowledge Gap: Existing literature predominantly focuses on private sector financial accounting, leaving the impact of public organizational structure on cost accounting systems underexplored. Aims: This study evaluates how organizational complexity, formalization, and centralization influence cost accounting information system effectiveness within Iraqi higher education. Results: Structural equation modeling indicates that complexity and formalization significantly enhance system quality and control standardization, whereas centralization negatively affects information flow speed. Novelty: This research provides an empirical model integrating Contingency Theory and Information Processing Theory within public university cost management. Implications: Policy makers must implement activity-based costing and integrated enterprise resource planning systems while balancing decentralization to optimize public financial management. Keywords : Organizational Structure, Cost Accounting Information Systems, Higher Education, Activity-Based Costing, Public Financial Management Key Findings Highlights Structural complexity and formalization significantly enhance accounting information quality and control standardization. High administrative centralization delays accounting information flow and slows down strategic decision-making. Implementing activity-based costing and integrated digital platforms optimizes public higher education resource management.